Relationship between Body Weight and Linear Body Measurements in Japanese Quail (Coturnix coturnix japonica) - Victoria, O.; Fayeye, T. R.; Ayorinde, K. Luke; Olojede, H. (Journal of Scientific Research, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> A total of 108 two-weeks-old Japanese quail chicks were used to study the relationship between body weight and linear measurements and to predict body weight from linear measurements of body length (BL), body girth (BG), wing length (WL), shank length (SL), shank diameter (SD) and drum stick (DS).The results showed that the mean quail birds body weights were 35.23g and 143.78g, at 2nd and 8th weeks, respectively. Body weight gain was increased between 2 and 6 weeks of age and thereafter decreased with advancing age. Female birds were significantly (P< 0.05) heavier than those of male counterpart at 6th and 8th weeks of age. Significantly positive correlations (P<0.01) were obtained between body weight and body measurements at 2nd, 4th and 8th weeks. The best correlation was obtained between body weight and body girth at the 2nd week of age (0.70). The estimates of coefficient of determination and predictive equations show that body weight in Japanese quail is linearly related to body measurements especially with body girth and body length. The study shows that it is possible for breeders to use BG and BL as criteria for assessment and early selection of Japanese quail for body weight. Keywords: Japanese quail; Body weight; Linear measurements; Correlation © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i1.16368 J. Sci. Res. 6 (1), 175-183 (2014)